(untitled) (The Review of Diabetic Studies, 2024)
The use of X-rays for imaging has a long history, which has resulted in several well-established methods in preclinical as well as clinical applications, such as tomographic imaging or computed tomography. While projection radiography provides anatomical information, X-ray fluorescence analysis allows quantitative mapping of different elements in samples of interest. This comprehensive review aims to explore the various applications of X-ray imaging in biomedical research by analyzing existing literature and summarizing key findings. The study used secondary data sources, including research articles, reviews, and textbooks, to compile a detailed overview of the different imaging modalities and techniques available in X-ray imaging. The review covers a wide range of biomedical research areas where X-ray imaging has been employed, including anatomy, physiology, pathology, and pharmacology. It examines how X-ray imaging techniques such as radiography, computed tomography (CT), and micro-CT have been used to study bone structure, vascular system, cancer, and drug delivery in animal models and human subjects. The review also highlights the advancements in X-ray imaging technology, such as the development of synchrotron radiation facilities and high-resolution imaging techniques, which have significantly improved the quality and accuracy of biomedical imaging. In conclusion, this review stresses the significance of X-ray imaging in advancing biomedical research and highlights its potential for future applications in understanding disease mechanisms, developing new therapeutic strategies, and improving patient care.